Actinedida e Acaridida (Arachnida: Acari) edáficos de Piracicaba, Estado de São Paulo - Mineiro, Jeferson L. De C. [UNESP]; De Moraes, Gilberto J. (My University, 2002)
The objective of this work was to identify the edaphic mites of the suborders Actinedida and Acaridida collected on the campus Luiz de Queiroz, University of São Paulo. Soil samples were taken from three different environments, i.e., a residual secondary forest, a perennial crop represented by a rubber tree plantation (Hevea brasiliensis Müll. Arg.), clone RRIM 600, and an area of annual crops (corn followed by beans). Litter samples were taken only from the secondary forest and the rubber tree plantation. Mites were extracted using a modified Berlese-Tullgren apparatus. A total of 32 species belonging to 22 genera of 14 families of the suborder Actinedida was found in soil and litter. Eupodidae mites were the most numerous in both substrates in the three environments. Eupodes sp.2 (Eupodidae) was the most numerous species. A total of seven species belonging to six genera of four families of the suborder Acaridida was found. Acaridae was the most numerous family in this suborder in both soil and litter of all three environments, with a predominance of a species of Tyrophagus.
Edaphic Actinedida e Acaridida (Arachnida: Acari) from Piracicaba, State of São Paulo, Brazil
Keywords: Ecology; Soil mites; Taxonomy